(3GdfXGe GdbGfhfj dTQcI GdhSGWI aj Shb GdChQGb GdeGdjI (B:s (3OQGSI ebGQfI (B/s - (3ehdhO, QjRGfs ((3HjQhJ (B:s (3efThQGJ GdMdHj GdMbhbjI,s, 2015)
(3CgejI gPg GdOQGSI Jcef aj CfgG JfGhdJ GdfXGe GdbGfhfj dTQcI GdhSGWI GdeGdjI HUhQI eaUdI ef YQV JYQjagG hNUGFUgG hJejjRgG YeG jTJHg HgG hGdHMK aj Cge GdGdJRGeGJ GdedbGI Ydi YGJbgG ebGHd GdMbhb GdJj JJeJY HgG, HGdEVGaI Edi OQGSI cjajI JCSjS TQcI GdhSGWI GdeGdjI hEOGQJgG heOi eQGYGI GdbhGfjf GdebGQfI dNUhUjI Jdc GdTQcI aj eQMdI JSjSjgG hEOGQJgG(B. (3ceG JWQbJ GdOQGSI Edi cjajI Jchjf QCS eGd GdTQcI hCfhGY GdMUU GdebOeI ajg hGdQbGHI Ydi COGFgG hGdLgGJ GdJj Jbhe HgPg GdegeI(B. (3HGdEVGaI Edi cd eG JbOe JfGhdJ GdOQGSI eOi JMbb GdeSDhdjI GdbGfhfjI HCfhGYgG GdeNJdaI aj MGdI ENdGd GdTQcI HCMO GdJRGeGJgG GdbGfhfjI Ch GdYbOjI Ch GdbhGYO GdeJYdbI HGdMaGX Ydi JhGRf Shb GdChQGb GdeGdjI(B. (3ceG JfGhdJ GdOQGSI WQb GfbVGA TQcI GdhSGWI GdeGdjI(B. (3YQVJ GdOQGSI ehGba GdbhGfjf GdebGQfI ERGA GdehGVjY GdeWQhMI ajgG hHjfJ ehGbY GdbUhQ(B. (3hGfJgJ GdOQGSI HLedI ef GdGSJfJGLGJ hGdJhUjGJ GdebJQMI Ydi GdeTQY GdYQGbj hPdc HJYOjd LedI ef GdfUhU GdbGfhfjI GdhGQOI aj bGfhf GdTQcGJ hGdbGfhf GdeDbJ dCShGb GdChQGb GdeGdjI(B. (3HGdEVGaI Edi GdJhUjI HLedI ef GdebJQMGJ GdJj ef GdVQhQj Cf JYcS Ydi GdbGfhf GdPj ef GdVQhQj EUOGQg dJfXje Shb GdeGd HUhQI YGeI aj GdYQGb(B.s
(3HHdjhLQGajI (B: (3UaMI (B367-378.s
Keywords: (3GdChQGb GdeGdjIs -- (3bhGfjf hJTQjYGJs -- (3GdYQGbs; (3GdHhQUGJs -- (3bhGfjf hJTQjYGJs -- (3GdYQGbs